A social licence for science: capturing the public or co-constructing research? - Raman, Sujatha; Mohr, Alison (Routledge, 2014)
The “social licence to operate” has been invoked in science policy discussions including the 2007 Universal Ethical Code for scientists issued by the UK Government Office for Science. Drawing from sociological research on social licence and STS interventions in science policy, the authors explore the relevance of expectations of a social licence for scientific research and scientific contributions to public decision-making, and what might be involved in seeking to create one. The process of seeking a social licence is not the same as trying to create public or community acceptance for a project whose boundaries and aims have already been fully defined prior to engagement. Such attempts to “capture” the public might be successful from time to time but their legitimacy is open to question especially where their engagement with alternative research futures is “thin”. Contrasting a national dialogue on stem cells with the early history of research into bioenergy, we argue that social licence activities need to be open to a “thicker” engagement with the social. Co-constructing a licence suggests a reciprocal relationship between the social and the scientific with obligations for public and private institutions that shape and are shaped by science, rather than just science alone.